Analisis Kondisi Rumah Sebagai Faktor Risiko Kejadian Pneumonia Pada Balita di Wilayah Puskesmas Sentosa Baru Kota Medan Tahun 2008 - Sinaga, Lenni Arta F.S.; Suhartono, Suhartono; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background: House Condition (Solar orientation, temperature quality, degree of humidity, ventilation index and occupancy density)  are several factors may cause infection of diseases and health disorders, among other are infection of respiratory tract such as common cold, tuberculosis, influenza, pneumonia and so on. In 2007, there were 7713 cases of pneumonia in Medan city. In the working area of Sentosa Baru Health Center had the highest with 770 cases (10 %). Sentosa Baru was one of subdistrict which had the biggest population in Medan that cause many problems specially to provide good house. This study aimed to analyze house condition (solar orientation, temperature quality, degree of humidity, ventilation index and occupancy density) in relation to pneumonia incidnence. Method: It was a case control study  carried out on August to October 2008 at Sentosa Baru Health Center in Medan. Children qualifying pneumonia classification were defined as cases (62) and without pneumonia as controls (62). Analysis by Chi-Square test and stratification by Mantel Haenszel method. Result: The result of the research showed that solar orientation had OR = 2,9 ( 95% CI =1,28 -6,70), ventilation index (OR = 2,9 ; 95% CI  = 1,27 -,6,70) , and living in crowded home (OR = 6,9  ; 95% CI =  2,72 -  17,52) were risk factors for pneumonia incidence. Multiple Regresion Analysis showed that living in crowded home was the most dominant risk factor for pneumonia under five years children at Sentosa Baru Public Health Medan City 2008. Key word : family behavior and pneumonia incidence